A crash course in Mathematica - Kaufmann, Stephan, 1951- (Boston : Birkhauser Verlag, 1999)
"A Crash Course in Mathematica" is a compact introduction to the program Mathematica, which is widely used in mathematics, as well as in the natural and engineering sciences.